Reprint: The impact of critical thinking disposition on learning using business simulations. Issue 3 (November 2015) - Bell, Robin; Loon, Mark
Abstract: This research seeks to determine the relationship between students' critical thinking disposition and their learning while engaging in a business simulation at a UK higher education institution (HEI). The research informs educators making decisions about the use of simulations as to the value of considering critical thinking dispositions. Previous research has found that simulations are an effective way for students to engage actively in learning, bridging the gap between theory and practice. It has also been found that such simulations can develop students' critical thinking skills. However, hitherto no research has been undertaken into the role that existing critical thinking disposition has on the learning of students, as measured by the degree to which students perceived that they met the module's intended learning outcomes. This research offers insights into the role and importance of critical thinking disposition and its component dimensions and how this impacts student learning. The results indicate that the level of critical thinking disposition is positively related to the students' learning. The implications of the research suggest educators should target business simulations at specific cohorts of students. The relative importance of the critical thinking disposition constructs and the practical educational implications of these findings are discussed. Highlights: The impact of critical thinking disposition on student learning using simulations. Critical thinking disposition was positively related to improved student learning. The cognitive maturity and engagement dimensions were both positively related. The role and value of developing critical thinking disposition is discussed.